Makna Tradisi Sedekah Laut dI Desa Tasik Agung Rembang dalam Perspektif Teori Interaksionalisme Simbolik - Siti Markhamah; Yusuf Falaq (UPT Pusat Studi Aswaja UNISNU Jepara, 2023)
AbstractIndonesia is rich in culture and traditions. Each region in Indonesia has different traditions, tribes and cultures and has a belief system that smells of myth. Since the time of the ancestors of the Indonesian people, they have believed in the existence of supernatural powers that govern the life of the universe. This is evidenced by the discovery of various historical records about various kinds of traditional ceremonies, traditions and rituals. One of them is the sea alms tradition which is still preserved by the residents in the village of Tasik Agung Rembang. This sea alms tradition is always held lively and lively. The sea alms tradition is a hereditary tradition that has existed since ancient times. In the celebration of the traditional sea alms ceremony, it contains many symbols. Of the many symbols that exist in this sea alms tradition, none can clearly explain the meanings of the symbols used and used in the celebration of the tradition because everyone has a different point of view in interpreting it. This study aims to describe the meanings of symbols in the traditional sea alms ceremony in Tasik Agung village, Rembang. The benefit of this research is to add to the literature on the meaning of the celebration symbol at the sea alms tradition ceremony. This study uses a qualitative descriptive method that is to analyze and then clearly describe the problem that comes from a literature review. Sources of data used in this study in the form of secondary data. The results of the study indicate that the sea alms tradition is a hereditary ritual from the time of the ancestors as a salvation ceremony by performing larung offerings. The meaning of these symbols is closely related to the theory of symbolic interactionism because the symbols in the sea alms tradition have previously been mutually agreed upon to determine actions in everyday life. Symbols are needed to understand something that is beyond the reach of human reason. The forms of symbols in the sea alms tradition are classified into three, namely in the form of actions, objects, expressions, and places.Keywords: Culture, Sea Alms Tradition, Symbolic InteractionalismAbstrakIndonesia kaya akan budaya dan tradisi. Setiap daerah di Indonesia mempunyai tradisi, suku dan budaya yang berbeda-beda serta memiliki aliran kepercayaan yang berbau mitos. Sejak zaman nenek moyang bangsa Indonesia telah mempercayai adanya kekuatan gaib yang mengatur kehidupan alam semesta. Hal ini terbukti dengan banyak ditemukannya berbagai catatan sejarah tentang berbagai macam upacara adat, tradisi dan ritual. Salah satunya adalah tradisi sedekah laut yang masih dilestarikan penduduk di desa Tasik Agung Rembang. Tradisi sedekah laut ini selalu diadakan secara meriah dan semarak. Tradisi sedekah laut merupakan tradisi turun temurun yang sudah ada sejak zaman dahulu. Di dalam perayaan upacara tradisi sedekah laut tersebut mengandung banyak simbol. Dari banyaknya simbol yang ada pada tradisi sedekah laut ini, tidak ada yang bisa menjelaskan secara lugas mengenai makna-makna simbol yang ada dan digunakan dalam perayaan tradisi tersebut karena setiap orang mempunyai sudut pandang yang berbeda dalam menafsirkannya. Penelitian ini bertujuan untuk mendeskripsikan makna-makna simbol yang ada dalam upacara tradisi sedekah laut di desa Tasik Agung, Rembang. Manfaat penelitian ini adalah menambah literatur tentang makna simbol perayaan pada upacara tradisi sedekah laut. Penelitian ini menggunakan metode deskriptif kualitatif yaitu menganalisis dan kemudian dengan jelas menggambarkan masalah yang bersumber dari tinjauan literatur. Sumber data yang digunakan dalam penelitian ini berupa data sekunder. Adapun hasil penelitian menunjukkan bahwa tradisi sedekah laut merupakan ritual turun temurun dari zaman nenek moyang sebagai upacara selamatan dengan melakukan larung sesaji. Makna simbol tersebut berkaitan erat dengan teori interaksionalisme simbolik karena simbol-simbol pada tradisi sedekah laut sebelumnya telah disepakati bersama untuk menentukan tindakan di kehidupan sehari-hari. Simbol-simbol diperlukan untuk memahami sesuatu yang berada di luar jangkauan rasio manusia. Bentuk-bentuk simbol dalam tradisi sedekah laut ini diklasifikasikan menjadi tiga, yaitu berupa tindakan, benda, ungkapan dan tempat.Kata Kunci: Budaya, Tradisi Sedekah Laut, Interaksionalisme Simbolik